First Record of a Polystome from Alligator Snapping Turtle, Macrochelys temminckii (Cryptodira: Chelydridae) or Mississippi; with Comments on “Neopolystoma orbiculare (Stunkard, 1916)” and Its Junior Subjective Synonyms - (:unkn) unknown (My University, 2021)
Herein, we describe several newly-collected specimens of Neopolystoma cf. orbiculare from the urinary bladder of 2 alligator snapping turtles, Macrochelys temminckii (Troost in Harland, 1835) (Cryptodira: Chelydridae Gray, 1831) from Comet Lake (30°35′46.94″N, 88°36′3.12″W), Pascagoula River, Mississippi. Our specimens differed from all previous descriptions of N. orbiculare and its junior subjective synonyms by the combination of having intestinal ceca adorned with triangular pockets and that terminate dorsal to the haptor, distinctive hooklets each having a handle and guard of approximately equal length and having a much longer and curved blade, 16 genital coronet spines that each possess 1–2 flanges per spine, pre-testicular vaginal pores, and vaginal ducts that are anterior to the junction of the oviduct and genito-intestinal canal. Some of our specimens were enantiomorphic (4 and 3 had a dextral and sinistral ovary, respectively). Nucleotide sequences (large subunit ribosomal DNA [28S], small subunit ribosomal DNA [18S], and cytochrome oxidase subunit 1 mitochondrial gene [COI]) for our specimens were most similar to GenBank sequences ascribed to N. orbiculare. Single-gene and concatenated phylogenetic analyses confirmed that NeopolystomaPrice, 1939 is polyphyletic and that our isolates share a recent common ancestor with those ascribed to N. orbiculare. This is the first record of a polystomatid from Mississippi, from the Pascagoula River, and from the alligator snapping turtle (and only the second species of Neopolystoma reported from any snapping turtle).
Keywords: African Research